2015
DOI: 10.1159/000370307
|View full text |Cite
|
Sign up to set email alerts
|

The Agreement between the MMSE and IQCODE Tests in a Community-Based Sample of Subjects Aged 70 Years or Older Receiving In-Home Nursing: An Explorative Study

Abstract: Aim: It was the aim of this study to compare the Mini-Mental State Examination (MMSE) with the Informant Questionnaire for Cognitive Decline in the Elderly (IQCODE) and to explore the characteristics of subjects with possible dementia with only one of the two tools. Methods: We used a random sample of patients aged 70+ receiving social service or in-home nursing. The patients were tested with the MMSE, and the next of kin was interviewed using the following: the IQCODE, the Cornell Scale for Depression in Deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…To summarize, most studies conclude that the IQCODE can be used to identify patients with signs of dementia [27]. Cross-validation studies between the IQCODE and other similar informant questionnaires and cognitive tests have been conducted showing that informant-based measures seem to be reliable in identifying cognitive changes in patients with AD [27,28,29], but studies also emphasize the risk of biases [30,31,32,33]. Burden of care and the patient's behavior are two important factors that could bias the IQCODE rating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, most studies conclude that the IQCODE can be used to identify patients with signs of dementia [27]. Cross-validation studies between the IQCODE and other similar informant questionnaires and cognitive tests have been conducted showing that informant-based measures seem to be reliable in identifying cognitive changes in patients with AD [27,28,29], but studies also emphasize the risk of biases [30,31,32,33]. Burden of care and the patient's behavior are two important factors that could bias the IQCODE rating.…”
Section: Introductionmentioning
confidence: 99%
“…We found only a few studies examining the relationship between neuropsychiatric symptoms in the patient and the IQCODE rating. Two studies found a significant correlation between neuropsychiatric symptoms and the IQCODE rating [33,36], whereas another found no correlation [37]. Thus, this association needs to be studied further.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies included gender as a potential correlate. Although three of these concluded that IRCD, as reported by the IQCODE, was not significantly associated with patient gender (Farias et al., 2004; Kirkevold & Selbaek, 2015; Nygaard et al., 2009), two reported a significant, albeit weak, association. Jorm et al (1994) identified a trend for informants to report greater cognitive decline on a survey of male patients, whilst Persson et al.…”
Section: Resultsmentioning
confidence: 96%
“…Seven studies examined the relationship between patient age and IRCD. Five found a positive association between age and IRCD without controlling for other variables; with informants reporting significantly greater cognitive decline on a survey (Jorm et al., 1994) and the IQCODE (Farias, Mungas, Reed, Haan, & Jagust, 2004; Kirkevold & Selbaek, 2015; Nygaard, Naik, & Geitung, 2009; Persson, Braekhus, Selbaek, Kirkevold, & Engedal, 2015) with increasing age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation